An investigation into the theorectical construction of effort and maximum effort as a contribution to the theory of creative ability - Sherwood, Wendy Jayne (My University, 2016)
This thesis is concerned with the occupational therapy profession's development of its theoretical basis for practice. In an occupational therapy theory entitled the Theory of Creative Ability, the concepts effort and maximum effort are hypothesised to be essential to activity participation. A critical evaluation of the Theory of Creative Ability in this thesis identifies that effort is not defined, and maximum effort is inadequately defined, which makes the theory weak and potentially operationally inadequate. Furthermore, there is little evidence that effort is a construct that is well understood in the occupational therapy profession. The purpose of the current study was to discover the theoretical construction of effort as a contribution to the Theory of Creative Ability, and to the occupational therapy profession as a whole. Using Grounded Theory Methodology, the study analysed data from 11 occupational therapists in South Africa, 7 occupational therapists in the United Kingdom (UK), 29 patients receiving occupational therapy in mental health and physical health care in South Africa, and 24 members of the public in the UK. Field observations of occupational therapy with patients in South Africa, the literature and the media, were also data for analysis. The resulting emergent grounded theory was then verified as plausible by occupational therapists and members of the public in an on-line focus group. A full literature review was then undertaken for integration, leading to minor modifications to the grounded theory. Key aspects of the theory were aligned with the Theory of Creative Ability. Many aspects of the grounded theory were compatible, but that there are differences in how minimal and maximum effort are conceptualised in relation to activity participation. Finally, a formal grounded Theory of Effort for Relating was developed as a result of conceptual comparison of the emergent grounded theory with other theoretical works. At the heart of the formal grounded theory is the discovery that effort is a fundamental criterion of the self, essential for relating an individual to himself and the world. The formal grounded theory explains effort as varying in quantity and quality as a reflection of the quantity and quality of one's motivation and total resources. The conditions, observable referents, and consequences of effort are explained. A decision-making process, leading to a decision for effort, and ultimately to the quantity and quality of one's effort, is also explained.
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy Johannesburg 2016